Induction of labour versus expectant monitoring in women with pregnancy induced hypertension or mild preeclampsia at term: the HYPITAT trial - Mol Ben WJ; van Loon Aren J; le Cessie Saskia; Kwee Anneke; Huisjes Anjoke JM; de Groot Christianne JM; Franx Arie; Drogtrop Addi P; Bloemenkamp Kitty WM; Birnie Erwin; Burggraaff Jan M; van den Berg Paul P; et al. (BMC, 2007)
Abstract Background Hypertensive disorders, i.e. pregnancy induced hypertension and preeclampsia, complicate 10 to15% of all pregnancies at term and are a major cause of maternal and perinatal morbidity and mortality. The only causal treatment is delivery. In case of preterm pregnancies conservative management is advocated if the risks for mother and child remain acceptable. In contrast, there is no consensus on how to manage mild hypertensive disease in pregnancies at term. Induction of labour might prevent maternal and neonatal complications at the expense of increased instrumental vaginal delivery rates and caesarean section rates. Methods/Design Women with a pregnancy complicated by pregnancy induced hypertension or mild preeclampsia at a gestational age between 36+0 and 41+0 weeks will be asked to participate in a multi-centre randomised controlled trial. Women will be randomised to either induction of labour or expectant management for spontaneous delivery. The primary outcome of this study is severe maternal morbidity, which can be complicated by maternal mortality in rare cases. Secondary outcome measures are neonatal mortality and morbidity, caesarean and vaginal instrumental delivery rates, maternal quality of life and costs. Analysis will be by intention to treat. In total, 720 pregnant women have to be randomised to show a reduction in severe maternal complications of hypertensive disease from 12 to 6%. Discussion This trial will provide evidence as to whether or not induction of labour in women with pregnancy induced hypertension or mild preeclampsia (nearly) at term is an effective treatment to prevent severe maternal complications. Trial Registration The protocol is registered in the clinical trial register number ISRCTN08132825.